Health economic analysis of curative‐intent gastrectomy for gastric carcinoma and the costs related to post‐operative complications. Issue 1 (2nd June 2020) - Sivakumar, Jonathan; Alnimri, Feras; Johnson, Mary A.; Ward, Salena; Chong, Lynn; Hii, Michael W.
Abstract : The objectives of this study were to perform a cost‐analysis of admissions following gastrectomy for gastric carcinoma. The presence and severity of post‐operative complications is strongly associated with increasing cost. Minimizing complications, in addition to obvious clinical benefits, enables a large reduction in costs of care. Abstract: Background: The management of post‐gastrectomy complications requires considerable resources and is likely associated with a substantial economic burden. The objectives of this study were to perform a cost analysis of admissions following gastrectomy for gastric carcinoma and then to quantify the financial impact of post‐operative complications. Methods: A retrospective analysis was conducted in patients that underwent a gastrectomy from 2008 to 2019. Demographic data, operative information, post‐operative complications and facility costs were compared. Results: A total of 74 patients underwent a curative‐intent gastrectomy during the study period. The 36 (48.6%) patients that had no complications had a median total admission cost of AU$29 228. A total of 21 (28.4%) patients had a minor complication and 17 (23.0%) patients had a major complication, with a median total admission cost of AU$36 592 and AU$71 808, respectively. The difference across all three groups was statistically significant. In patients who had major complications compared to those without complications, there was a significant increase in the cost of intensive care services, theatre resources and nursing care. Across the whole cohort, the principal cost centres accounting for the largest proportion of total cost were theatre equipment and resources (33.9%), nursing care on the ward (23.0%) and staffing time of the surgical team (16.7%). Conclusion: The surgical management of gastric cancer carries a substantial cost burden. The presence and severity of post‐operative complications is strongly associated with increasing cost. Minimizing complications, in addition to obvious clinical benefits, enables a large reduction in costs of care.